Development and control of a 5-DOF robotic arm using forward kinematics and IoT integration - Mohd Riduwan, Ghazali; Mohd Ashraf, Ahmad; Noor Asma' Shahirah, Yuseri; Mohd Helmi, Suid (Association for Computing Machinery, 2024)
This paper explores the design and implementation of a robotic arm system, integrating theoretical concepts and practical applications. The aim is to develop an effective robotic arm for educational and practical uses, addressing the need for precise forward kinematic control based on the Homogeneous Transformation Matrices (HTM) method and implementing IoT-based control using a microcontroller. The method involves the design and construction of a five-degree-of-freedom (DOF) robotic arm, the integration of servo motors, and the development of control systems using RemoteXY and Arduino IDE. The results from testing and experiments demonstrate the robotic arm's ability to track the desired movement angle and display the HTM information, consisting of rotational and positional data of the robot flange via IoT. This project successfully combines theoretical knowledge with practical implementation, resulting in a functional and versatile robotic arm that serves as a valuable teaching aid and practical tool in the basic robotics concept of forward kinematics for a robotic arm system.